Characterization of the etiological structure and genotypically determined phenotypic resistance to carbapenems of infectious complications leading pathogens in critically ill patients - Nazarchuk, O. A. (Zaporozhye Medical Journal, 2018)
The aim is to investigate the genotypically determined phenotypic resistance to carbapenems of gram-negative microorganisms isolated from patients with critical states. Material and methods. Microbiological etiology of infectious complications in critically ill patients (n = 726) was investigated. In total, during the years 2011–2016, 933 clinical strains of infectious complications pathogens from patients with severe burns (n = 435) and from patients treated in intensive care units (n = 291) were isolated and identified. The sensitivity of microorganisms clinical isolates to antibiotics was investigated by means of the standard microbiological methods. In gram-negative bacteria resistant to carbapenems, a molecular genetic study of mechanisms of resistance, determined by the presence of VIM genes, was carried out using the method of real-time polymerase chain reaction. Results. Studies have shown that gram-negative microorganisms (Acinetobacter spp. – 36.3 %, P. aeruginosa – 31.7 %, Enterobacter spp. – 13.5 %, Proteus spp. – 7.9 %, E. coli – 3.8 %; K. pneumoniae – 3.6 %, etc.) account for a significant part of infectious complications pathogens structure in critically ill patients. A. baumannii strains (67 %) have expressed phenotypic resistance to most antibiotics, in particular to carbapenems (up to 63.2 %). Poly-antibiotic resistance was also found in P. aeruginosa (72 %), and above one the 3rd part of strains of this pathogen was found to have phenotypic resistance to carbapenems. In-depth study of molecular genetic determinants of the resistance mechanism to β-lactam antibiotics among clinical strains of gram-negative bacteria there was proved VIM-induced resistance to carbapenems in A. baumannii, P. aeruginosa, P. mirabilis. Conclusions. Enterobacteriaceae and non-fermenting gram-negative microorganisms (P. aeruginosa, P. mirabilis, A. baumannii), which are the leading causative agents of infectious complications in patients with severe burns and critically ill ones, phenotypically develop low sensitivity to carbapenems, which is genetically determined in 12.3 % by VIM genes expression.